THE SECOND INTIFADA AND THE ISRAELI-PALESTINIAN CONFLICT - Wang, Yilin (PEOPLE: International Journal of Social Sciences, 2020)
The leader of the Likud Party in Israel, Ariel Sharon, had made a contentious visit to the Temple Mount in Jerusalem on September 28, 2000. Such an unprecedented move immediately gave rise to the outbreak of the second intifada, in which the President of Palestinian Authority, Yasser Arafat, unleashed Palestinian militias as a defensive response to Sharon's inconsiderate behave. The second intifada not only triggered a great hostility and intensive debate among Jerusalem, but also revealed a series of reasons contributing to increasingly descend in mutual suspicion, discontent, and conflicts. The researcher used secondary resources, such as articles, media, and books, to examine explanations of the failure to unite Israel and Palestine, which were divided into the failure of the past attempts, and negotiations giving endless space for governors to enact self-centred policies continued illegal military occupation over Palestinian territory, and conventional as well as obstinate demanding and belief in Jerusalem. However, this political and ethical struggle also helped to appeal to combined emotion of indignation and worry from younger generations to their domestic respondents, as well as inferred the danger and urgency to have a third-party helping to detail an effective and explicit resolution to reverse the status quo.